Factors influencing predator roadkills: the availability of prey in road verges - Silva, Maria do Carmo (2020)
Road mortality is the most noticeable effect of roads on wildlife. Road verges may provide important refuges for small mammals and rabbits, particularly when roads cross intensive agricultural or grazed areas. In these circumstances, the increasing use of verges by prey species may attract predators to road surroundings increasing the risk of roadkill. The aim of this study was to quantify the role of prey availability (small mammals and rabbits) on predator road casualties, taking into account road and surrounding landscape characteristics. We analyzed this effect on different predator species, such as, snakes, owls and mammal carnivores. The study took place in a 10 km stretch of a National Road (EN4) in southern Portugal. Relationships among predator mortality and explanatory variables (prey abundance, landscape characteristics, and road verge features) were evaluated using Multivariate Redundancy Analysis (RDA) followed by a variation partitioning. Our results show that, although landscape features explained most of the mortality variation, the prey availability was also very important. Roadkills of Montpellier snake and Egyptian mongoose are strongly associated with wild rabbit abundance on verges, while mortality of stone marten, barn owl and tawny owl is related with wood mouse abundance, Mediterranean forest (montado) density, and verge shrub density. Implications for verge management and implementation of mitigation actions are discussed. We suggest vegetation removal in verges to decrease shelter and food availability for prey, and/or the promotion of habitat for prey in areas distant from roads.